215k views
7 votes
Answers for the 2 boxes please:)​

Answers for the 2 boxes please:)​-example-1

1 Answer

8 votes

Answer:

(1,2)

Explanation:

Eliminate y-term


(x + 2x) + (4y - 4y) = 9 - 6 \\ 3x = 3 \\ x = (3)/(3) \\ x = 1

Substitute x = 1 in any given equations.

I choose to substitute in the first equation.


x + 4y = 9 \\ 1 + 4y = 9 \\ 4y = 9 - 1 \\ 4y = 8 \\ y = (8)/(4) \\ y = 2

Answer Check

Substitute both x-value and y-value in any given equations.


x + 4y = 9 \\ 1 + 4(2) = 9 \\ 1 + 8 = 9 \\ 9 = 9

The first equation is true. However, we have to check the second equation as well. (Although the first true equarion has already raised the high possibility of right answer.)


2x - 4y = - 6 \\ 2(1) - 4(2) = - 6 \\ 2 - 8 = - 6 \\ - 6 = - 6

Both equations are true for (1,2). Thus the answer is (1,2)

User Pkario
by
5.9k points